(untitled) (Journal of Nobel Medical College, 2013)
Introduction: Due to regular exercises, athletes tend to have an increase in pulmonary capacity when compared to non-exercising individuals. Intensity and severity of sports engaged in by the athletes probably determines the extent of strengthening of the inspiratory muscles with a resultant increase in the pulmonary functions.1, 2 So, this study has been carried out to establish a relationship between the type of sports and pulmonary functions in Nepalese athletes. Methods: This study has adopted a cross sectional observational comparative research design. Spirometry was conducted in 84 different national level athletes [25.71 (± 4.55) years]. The athletes were from five different sport groups. Out of them, there were 16 weight lifters, 41 footballers, 10 swimmers, 8 marathon runners and 9 sprinters. Among them weight lifters, marathoners and sprinters were selected from the National sports council, Tripureshower, Kathmandu and footballers and swimmers were from the Nepal army club, Kathmandu, Nepal. The spirometry was done in sitting position using MIR SPIROLAB II spirometer based on American Thoracic Society (ATS) recommendations. Pulmonary function was assessed based on Forced Expiratory Volume in first second (FEV1), Forced Vital Capacity (FVC) and Peak Expiratory Flow Rate (PEFR) expressed as percent predicted for the age, sex, height, weight and race. Results: When comparing the mean values of FVC, FEV1 and PEFR among the five different sport groups, as expected, athletes who have more strenuous respiratory muscles exercise had significantly superior pulmonary function parameters. For example weight lifters and swimmers had 111.84 and 109.56 percentage of predicted values on FVC (P=0.008) respectively. But marathoners, footballers and sprinters had 105.83, 99.25 and 98.34 percentage of predicted values respectively. Similarly, weight lifters, swimmers, marathoners, footballers and sprinters had 110.63, 110.15 and 110.28, 102.52 and 99.23 percentages of predicted values on FEV1 (p=0.090) respectively. Swimmers, marathoners, footballers, weight lifters and sprinters had 106.03 and 107.34, 104.37, 102.08 and 86.58 percentage of predicted values on PEFR (p=0.027) respectively. Conclusion: Athletes who have most strenuous respiratory muscle exercise like swimming and weight lifting have better pulmonary function tests (PFTs) compared to other athletes like sprinters who have less strenuous muscle exercise. Journal of Nobel Medical College Vol. 2, No.1 Issue 3 Nov.-April 2013 Page 18-21 DOI: http://dx.doi.org/10.3126/jonmc.v2i1.7667